Matematyka
Spliteczka
3

Czy ktoś mógłby rozwiązać dwa ostatnie przykłady (na jutro POMOCY!!)

+0
(1) Odpowiedź
Nikii333

[latex]21c)\\\\(\frac{1}{2}\sqrt{2}+\frac{1}{4}\sqrt{2})^2= (\frac{1}{2}\sqrt{2})^2+2*\frac{1}{2}\sqrt{2}*\frac{1}{4}\sqrt{2}+(\frac{1}{4}\sqrt{2})^2= \frac{1}{4}*2+ *\frac{1}{4}*2 +\frac{1}{16}*2=\\\\= \frac{1}{2} + \frac{1}{2} +\frac{1}{8} =1\frac{1}{8}[/latex] [latex] (a+b)^2=a^2+2ab+b^2[/latex] [latex]d)\\\\( 3\sqrt[3]{2}- \sqrt[3]{2})^3= (3\sqrt[3]{2})^3-3 *(3\sqrt[3]{2})^2*\sqrt[3]{2}+3 * 3\sqrt[3]{2} *(\sqrt[3]{2})^2 - (\sqrt[3]{2})^3 =\\\\=27*2 -3 *9*\sqrt[3]{2^2*2} +9 *\sqrt[3]{2} *(\sqrt[3]{2^2*2} - 2 = 54 -27\sqrt[3]{8} +9 * \sqrt[3]{8} - 2 = \\\\= 54 -27*2 +9 *2 - 2 =54 -54 +18 - 2 = 16 \\\\\\(a-b)^3=a^3-3a^2b+3ab^2-b^3[/latex]

Dodaj swoją odpowiedź